PEMBELAJARAN ECOBRICK DALAM TEMA PENDIDIKAN LINGKUNGAN HIDUP DI SEKOLAH ALAM SUKAHAJI - Cica Nastika, - (2022)
This study discusses issues related to ecobrick learning in the theme of Environmental Education at the Sukahaji Nature School. This research can be used as a reference by teachers to develop learning related to Environmental Education, especially plastic waste management through the ecobrick method at the elementary school level. The purpose of this study is to describe the learning and management of ecobricks in the theme of Environmental Education at the Sukahaji Nature School. The approach in this study uses a qualitative descriptive approach through the case study method. The instruments used in this study were observation, questionnaires and interviews, accompanied by a study of documentation. The results and findings show that the flow of environmental education at the Alam Sukahaji School is not only taught orally, but environmental education is taught to friends of nature through direct practice. The activities include recycling plastic waste using the ecobrick method, giving trash every Thursday, and using used plastic cups as planting media. The conclusion of this study is that the management of plastic waste through the ecobrick method plays an important role in fostering love and concern for the environment for students at the Sukahaji Nature School. One of the activities related to the management of plastic waste is ecobricks which is carried out after friends of nature have finished snack time. The results of the management of this ecobricks are, students become more concerned about the environment and ecobricks made by friends of nature can be used as raw materials to make goods that have use value and selling value.